Dialogue about analysis methods in qualitative research: the discursive textual analysis in question (Revista Internacional de Formação de Professores, 2023)
The present study discusses the main methods of analysis in qualitative research (Content Analysis, Discourse Analysis, Analysis of Entangled Prose and Discursive Textual Analysis), with the aim of expanding knowledge about these methods and, more specifically, deepening the theoretical- methodological approach of Discursive Textual Analysis (DTA), an emerging method in the scientific field that presents assumptions with possibilities of use in research in the field of education. After presenting the theoretical foundations and procedures of DTA in a doctoral thesis, its effectiveness and suitability in analyzing data produced from teachers' narratives was evidenced.
Keywords: Methodology; Analysis Methods; Discursive Textual Analysis